2000
DOI: 10.1161/01.hyp.35.5.1135
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain–Induced Blood Pressure Elevation

Abstract: Abstract-This study was conducted to evaluate the mechanisms in weight gain-induced blood pressure (BP) elevation focusing, in particular, on the contributions of sympathetic nervous system activity, fasting plasma insulin, and leptin to BP levels. The study design was longitudinal with a cohort of 1897 men. BP, pulse rate, body mass index (BMI), fasting plasma norepinephrine (NE), insulin, and leptin were measured at 6 and 12 months in those 172 lean normotensive, 79 obese normotensive, 64 lean untreated hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 29 publications
7
103
1
1
Order By: Relevance
“…Only the subjects who had not changed their diet, exercise or body weight (45% provided in their biannual medical evaluation records) over the previous 6 months, including the run-in period of 1 month, were eligible for enrollment. 23,24 Randomization was stratified according to basal BP and body mass index (BMI). Average age at the baseline period was 38 ± 5 years for the diet alone group, 37±6 years for exercise alone group and 38±5 years for the combination of diet and exercise group.…”
Section: Methods Subjectsmentioning
confidence: 99%
“…Only the subjects who had not changed their diet, exercise or body weight (45% provided in their biannual medical evaluation records) over the previous 6 months, including the run-in period of 1 month, were eligible for enrollment. 23,24 Randomization was stratified according to basal BP and body mass index (BMI). Average age at the baseline period was 38 ± 5 years for the diet alone group, 37±6 years for exercise alone group and 38±5 years for the combination of diet and exercise group.…”
Section: Methods Subjectsmentioning
confidence: 99%
“…Only subjects whose body weight had not changed for at least the previous 1 year (weight change o5% provided in their biannual medical evaluation records) were enrolled in the present study. 17,29 The protocol was approved by the ethics committee of Osaka University Graduate School of Medicine, Japan, and written informed consent was obtained from all the subjects.…”
Section: Methods Subjectsmentioning
confidence: 99%
“…In many clinical and epidemiological studies, elevated sympathetic nervous activity has been documented in obesity 16 or weight gain [17][18][19] and in patients with end-stage renal disease. 7,[20][21][22] Zoccali et al 20,22 reported that the degree of sympathetic nervous activation might relate to the occurrence of fatal cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, insulin resistance has also been exhibited as an effect of heightened sympathetic drive, through b-adrenergic stimulation and/or vasoconstriction with subsequent reduction of muscular blood flow. 45,46 Leptin and neuropeptides Hyperleptinemia is another possible link between obesity and the development of hypertension. Leptin is a peptide hormone secreted from adipose tissue in direct proportion to adipose tissue mass.…”
Section: Function Of Hormones Insulinmentioning
confidence: 99%